Developing a program for enhancing youth HIV treatment adherence and risk reduction - Warunee Fongkaew (2018)
© 2017 John Wiley & Sons Australia, Ltd. Youth living with HIV face difficult and challenging situations that decrease their adherence to antiretroviral medications. In this study, we developed a pilot program to enhance HIV treatment adherence and risk reduction among youth living with HIV based on collaboration with a community hospital involving a multi-disciplinary healthcare team. Participants were 25 youth living with HIV/AIDS, 18 caregivers, and 12 healthcare providers. The action research process comprised a preliminary stage and four phases of assessment, planning, implementation, and evaluation. This program used “edutainment”, participatory learning, and multi-disciplinary collaboration to improve HIV treatment adherence and HIV risk behavior knowledge, motivation, and behavior. Education aimed to improve knowledge of antiretroviral drugs and HIV risk-taking behaviors. Motivation was directed at reframing beliefs and increasing positive attitudes of youth toward treatment adherence and raising awareness about safer sex behaviors. The behavioral skills focused on medication management in daily life activities, problem-solving, refusal and negotiation, and condom use. Findings provided preliminary evidence that the program was practical in a clinical context in a community hospital.